(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Automobiles have grown indispensable in our rapidly evolving environment. The dependability of a vehicle is just as important as its safety features. Disc brakes made of 6061 aluminium are the focus of this project’s design and study. Solidworks is used for modelling, and for thermal and structural reasons, Finite Element Analysis is run as a coupled field. Disc brakes that generate frictional heat undergo a transient finite element analysis (FEA) study of the thermoelastic contact problem (ANSYS). Prior to the distribution of temperatures, there was the thermal analysis, and in structural analysis, the distribution of stresses is done using the Ansys analysis programme. It is possible to model the disc brake’s thermoelastic behaviour under repeated braking conditions, which is a phenomenon that happens in disc brakes. In order to aid in the conceptual design of the disc brake system, the computational results for the distribution of heat flux and temperature on each friction surface between the contacting bodies are presented. The impact of material properties on the thermo elastic behaviours, specifically the maximum temperature on these surfaces, is also investigated. The investigation is carried out by contrasting the materials of grey cast iron and aluminium alloy 6061. Other properties, such wear resistance, are measured in accordance with ASTM guidelines. The acquired properties are contrasted with those of the preexisting material, grey cast iron. Compared to aluminium alloy 6061, grey cast iron performs better under thermoelastic circumstances.